Switching lanes: Exploring the strategic repositioning of the Kenyan tea industry. - Gatuguta, Susan Mwende (2006)
Research into the performance of primary commodities has shown a number of factors present in the global arena act as impediments to market stability. The tea industry is no exception to the rule as the global tea industry is facing a number of challenges which threaten the livelihood of tea producers. Tea producers have primarily focused on traditional primary commodities but this is not sustainable in future due to accelerated global competition. This paper seeks to look at the challenges and opportunities present for the Kenyan tea industry. In a bid to develop a strategic framework, the literature is drawn from the various areas of interest emerging from a recent pilot study conducted. The research looks at international trade and politics, routes to market for tea, capturing new markets and the value added approach. The evidence shows that Kenya is at a highly competitive advantage but is not utilizing its resources, both natural and created. Recommendations are directed towards adoption of the resource based view with an aim to create and sustain a new and improved competitive advantage.